Associations of Prenatal Exposure to Cadmium With Child Growth, Obesity, and Cardiometabolic Traits. Issue 1 (25th September 2018) - Chatzi, Leda; Ierodiakonou, Despo; Margetaki, Katerina; Vafeiadi, Marina; Chalkiadaki, Georgia; Roumeliotaki, Theano; Fthenou, Eleni; Pentheroudaki, Eirini; McConnell, Rob; Kogevinas, Manolis; Kippler, Maria
Abstract: Prenatal cadmium exposure has been associated with impaired fetal growth; much less is known about the impact during later childhood on growth and cardiometabolic traits. To elucidate the associations of prenatal cadmium exposure with child growth, adiposity, and cardiometabolic traits in 515 mother-child pairs in the Rhea Mother-Child Study cohort (Heraklion, Greece, 2007–2012), we measured urinary cadmium concentrations during early pregnancy and assessed their associations with repeated weight and height measurements (taken from birth through childhood), waist circumference, skinfold thickness, blood pressure, and serum lipid, leptin, and C-reactive protein levels at age 4 years. Adjusted linear, Poisson, and mixed-effects regression models were used, with interaction terms for child sex and maternal smoking added. Elevated prenatal cadmium levels (third tertile of urinary cadmium concentration (0.571–2.658 μg/L) vs. first (0.058–0.314 μg/L) and second (0.315–0.570 μg/L) tertiles combined) were significantly associated with a slower weight trajectory (per standard deviation score) in all children (β = −0.17, 95% confidence interval (CI): −0.32, −0.02) and a slower height trajectory in girls (β = −0.30, 95% CI: −0.52, −0.09; P for interaction = 0.025) and in children born to mothers who smoked during pregnancy (β = −0.48, 95% CI: −0.83, −1.13; P for interaction = 0.027). We concluded that prenatal cadmium exposure was associated with delayed growth in early childhood. Further research is needed to understand cadmium-related sex differences and the role of coexposure to maternal smoking during early pregnancy.